2007
DOI: 10.1111/j.1471-0528.2007.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the use of antenatal corticosteroids on mortality, cerebral lesions and 5‐year neurodevelopmental outcomes of very preterm infants: the EPIPAGE cohort study

Abstract: Objective To assess the impact of antenatal corticosteroids (ACS) on neonatal mortality, cerebral lesions and 5-year neurodevelopmental outcome of infants born at 24-27 and 28-32 weeks of gestational age (GA).Design Observational population-based study including all births at GAs between 22 and 32 weeks in 1997 in nine regions of France. Survivors were assessed at the age of 5 years.Sample and methods The population enrolled in the follow up comprised 2323 infants; there were 23 deaths before age 5 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 34 publications
6
22
0
3
Order By: Relevance
“…Analysis of the data collected during EPIPAGE study also showed the results comparable to ours (at 5 years of age, 20 and 10% of children born at 24 to 27 weeks of gestation and 28 to 32 weeks of GA, respectively, had CP). 12 However, in the study of Finnstrom et al…”
Section: 47mentioning
confidence: 95%
“…Analysis of the data collected during EPIPAGE study also showed the results comparable to ours (at 5 years of age, 20 and 10% of children born at 24 to 27 weeks of gestation and 28 to 32 weeks of GA, respectively, had CP). 12 However, in the study of Finnstrom et al…”
Section: 47mentioning
confidence: 95%
“…We also adjusted for prenatal steroids and sociodemographic factors depending on the outcome studied: for mortality, cerebral palsy and overall deficiencies, we adjusted for antenatal steroids as they are associated with these outcomes12 13; for MPC and overall deficiencies, we adjusted for sociodemographic factors including maternal age at birth, parity, maternal education, maternal birthplace and family social class, as they are known to be associated with cognitive outcomes. Family social class included the highest social class (father's or mother's), or the mother's social class if the mother was living alone 14 15.…”
Section: Methodsmentioning
confidence: 99%
“…Enfin, une diminution de la prévalence des leucomalacies périventriculaires cavitaires, composante de la maladie de la substance blanche sévère, a été notée dans les dernières années [17]. Elle pourrait être expliquée au moins en partie par un taux plus élevé de corticothérapie anténatale dont certaines études chez l'animal et chez le grand prématuré ont montré qu'elle était associée à une diminution des taux de leucomalacie cavitaire [18,19]. De plus, dans cet essai, une maladie de la substance blanche sévère n'a été observée sur les échographies transfontanellaires que dans moins de un cas sur deux des enfants avec une paralysie cérébrale ultérieure (45 % dans le groupe MgSO 4 et 40 % dans le groupe placebo).…”
Section: Limites De L'étudeunclassified